2016
DOI: 10.1515/jpem-2015-0123
|View full text |Cite
|
Sign up to set email alerts
|

Pubertal outcome in a female with virilizing adrenocortical carcinoma

Abstract: Adrenocortical tumors are neoplasms that rarely occur in pediatric patients. Adrenocortical carcinoma (ACC) is even more uncommon, and is an aggressive malignancy with 5-year survival of 55% in a registry series. There is a lack of information on long-term endocrine outcome in survivors. We describe a 10-year follow-up in a patient who presented at 3 years 5 months with a 1-year history of axillary odor and 6 months’ history of pubic hair development with an increased clitoral size. Androgen levels were increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 21 publications
2
7
0
Order By: Relevance
“…This predominance may explain why the majority of patients in this cohort had normal (79.3%) or tall stature (17.5%) and advanced BA (63.5%) at diagnosis of ACT, although most had M-ACT. This finding is in accordance with previous reports (18, 19, 24, 30, 31, 32, 34, 42, 43, 47). In addition, the combination of androgen and glucocorticoid effects may have accounted for the lack of difference in initial stature SDS, BMI SDS and Δ BA between V-ACT and M-ACT.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…This predominance may explain why the majority of patients in this cohort had normal (79.3%) or tall stature (17.5%) and advanced BA (63.5%) at diagnosis of ACT, although most had M-ACT. This finding is in accordance with previous reports (18, 19, 24, 30, 31, 32, 34, 42, 43, 47). In addition, the combination of androgen and glucocorticoid effects may have accounted for the lack of difference in initial stature SDS, BMI SDS and Δ BA between V-ACT and M-ACT.…”
Section: Discussionsupporting
confidence: 94%
“…Despite the acceleration of linear growth and skeletal maturation at diagnosis of ACT, there was a reduction of stature SDS from initial to final height, and the majority of patients (17 out of 19) reached normal FH. These results reinforce that growth tends to return to the patient’s predetermined channel after successful removal of an androgen-secreting ACT (47), with good prognosis on FH (18, 19, 30, 32).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…In females, severe hyperandrogenism causes virilization and hirsutism. In both sexes, it induces pseudopuberty and growth accelerations followed by growth arrest, muscle hypertrophy, deepening of the voice, and polycythemia . Data in the literature about the association between severe hyperandrogenism and erythrocytosis are scanty overall, and completely lacking in children .…”
Section: Biochemical Profile Of the Patient Evaluated Before And 2 mentioning
confidence: 99%
“…In both sexes, it induces pseudopuberty and growth accelerations followed by growth arrest, muscle hypertrophy, deepening of the voice, and polycythemia. [10][11][12] Data in the literature about the association between severe hyperandrogenism and erythrocytosis are scanty overall, and completely lacking in children. 12 Previous studies suggested that testosterone stimulates hematopoiesis in bone marrow stem cells and increases iron absorption at the intestinal level and its incorporation into erythrocytes.…”
mentioning
confidence: 99%